[OP.4D.03] IMPACT OF THE INHIBITION OF SOLUBLE EPOXIDE HYDROLASE ON CARDIOVASCULAR CONSEQUENCES OF CHRONIC KIDNEY DISEASE. (September 2016) - Hamzaoui, M.; Roche, C.; Lejeune, A.; Brunel, V.; Richard, V.; Bellien, J.; Guerrot, D.
Abstract : Objective: Cardiovascular (CV) events are more prevalent in chronic kidney disease (CKD) than in the general population, being the main cause of morbi-mortality. The aim of this project is to study the CV impact of the increase in the bioavailability of epoxyeicosatrienoic acids (EETs) by inhibiting soluble epoxide hydrolase (sEH) in the 5/6 nephrectomy model in 129/Sv mice. Design and method: 5/6 Nx mice were treated with the sEH inhibitor t-AUCB, a diuretic (amiloride), or placebo for 10 weeks. Echocardiography was performed one week before the sacrifice to assess heart function. Hearts were weighed and histologic analyses were performed to evaluate fibrosis. Vascular function was studied ex vivo on the mesenteric artery. Sequential blood and urine tests were performed to assess kidney function. Results: Following 5/6 Nx, mice developed CKD. The CV consequences were heart hypertrophy (heart weight/tibia length Nx 5/6 vs. Sham: 7, 9 ± 0, 3 vs. 6, 5 ± 0, 5 mg/mm, p < 0, 05), diastolic dysfunction (E/A ratio: Nx 5/6 vs. Sham: 1, 29 ± 0, 05 vs. 0, 97 ± 0, 04, p < 0, 001) and diffuse fibrosis (Nx 5/6 vs. Sham: 57, 8 ± 8, 8 vs. 1, 8 ± 1, 8 %, p < 0, 001). t-AUCB significantly prevented left ventricular hypertrophy (Nx 5/6 t-AUCB: 6, 7 ± 0, 2 mg/mm, p < 0, 05 vs. Nx 5/6), diastolic dysfunction (Nx 5/6 t-AUCB: 1, 12 ± 0, 04 p < 0, 05 vs. Nx 5/6), while beneficial effects on fibrosis were not significant (Nx 5/6 t-AUCB: 25, 0 ± 12, 7 % p: ns vs. Nx 5/6). No beneficial effects were present with amiloride. No vascular dysfunction was observed in our study. Conclusions: Inhibition of sEH reduces the CV consequences associated with CKD. The beneficial effects related to the increase in the bioavailability of EETs hold a therapeutic potential in CKD patients.